Dewatering of slurry with poor filterability in basket centrifuge: discharge of supernatant using bypass filter medium - Ginting, Alvin Najmuddin; Fukuyama, Ryo; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2015)
When centrifugal dewatering in basket centrifuge involves the sedimentation of particles in feed slurry, the slurry separates into two phases: supernatant and cake. The dewatering proceeds as the supernatant permeates through the cake. However, if the cake formed has poor permeability, it takes longer time to reach the desired moisture content. In this study , a new method is proposed to dewater slurry which forms cake with poor permeability and a comparison was made with the conventional design. In the proposed design, the filter media is placed not only on the circuit, but also at the bottom of the filter chamber. Thus, even though the cake formed has a high hydrodynamic resistance, the supernatant could be discharged because the filter medium at the bottom has less hydrodynamic resistance than the cake and therefore works as a bypass. It is known from the previous study that when the supernatant is totally discharged, the cake will undergo a consolidation process, which will make the cake more compact. Therefore, it is postulated that the bypass filter medium would improve the dewatering efficiency drastically. The results obtained is that the supernatant still remained in the filter chamber even after 300 s of dewatering when the conventional design was used, while the supernatant was completely discharged within 150 s when the new design was used. Thus, it can be concluded that the filter medium at the bottom of the filter chamber worked as a bypass and improved the dewatering performance.